Correlates of resistance and relapse during blinatumomab therapy for relapsed/refractory acute lymphoblastic leukemia. Issue 9 (5th June 2017) - Aldoss, Ibrahim; Song, Joo; Stiller, Tracey; Nguyen, Tina; Palmer, Joycelynne; O'Donnell, Margaret; Stein, Anthony S.; Marcucci, Guido; Forman, Stephen; Pullarkat, Vinod
Abstract: We retrospectively analyzed 65 patients with refractory/relapsed (r/r) ALL who were treated with blinatumomab for predictors of leukemia response as well as clinical patterns of relapse and resistance with particular focus on downregulation of CD19 expression and extramedullary disease (EM‐ALL). The complete remission (CR) rate was 51%, and 15 (45%) responders underwent allogeneic hematopoietic cell transplantation (HCT) in CR. High leukemia burden (bone marrow blasts >50%) ( P = .02), history of prior EM‐ALL ( P = .005), and active EM‐ALL at the time of initiating blinatumomab ( P = .05) predicted lower CR rate. Among refractory cases, 13 (41%) had evidence of EM‐ALL progression, and CD19 expression was negative or dim in 18% and 23%, respectively. Among responders, 20 (61%) subsequently relapsed among whom EM‐ALL relapse occurred in 8 (40%) patients, and CD19 expression was negative or dim in 35 and 6% of evaluable cases, respectively. Pretreatment moderate/strong CD19 expression ( P = .01) and history of prior EM‐ALL during ALL course ( P = .04) were risk factors for developing EM‐ALL at progression/relapse. However, no pretreatment factors predicted progression/relapse with CD19‐negative ALL. Overall‐survival (OS) and even‐free survival were improved for patients underwent allogeneic HCT compared to responders who did not. Furthermore, OS was superior for patients responded to blinatumomab compared to those who did not. Extramedullary and CD19‐negative disease are common during blinatumomab failure in r/r ALL. In addition to high leukemia burden, concurrent or prior history EM‐ALL were associated with lower response to blinatumomab. Higher CD19 expression as well as prior history of EM‐ALL were associated with EM‐ALL at the time of blinatumomab failure.